2020
DOI: 10.1038/s41467-020-19821-7
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR based editing of SIV proviral DNA in ART treated non-human primates

Abstract: Elimination of HIV DNA from infected individuals remains a challenge in medicine. Here, we demonstrate that intravenous inoculation of SIV-infected macaques, a well-accepted non-human primate model of HIV infection, with adeno-associated virus 9 (AAV9)-CRISPR/Cas9 gene editing construct designed for eliminating proviral SIV DNA, leads to broad distribution of editing molecules and precise cleavage and removal of fragments of the integrated proviral DNA from the genome of infected blood cells and tissues known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 27 publications
2
67
0
Order By: Relevance
“…Excision of HIV-1 proviral DNA in solid tissues and organs in humanized mice with chronic HIV-1 infection can be achieved via AAV-delivered CRISPR/Cas9 ( Yin et al, 2017 ). According to a recent study, AAV9-CRISPR/Cas9 gene editing was designed to eliminate simian immunodeficiency virus (SIV) proviral DNA in ART-treated non-human primates ( Mancuso et al, 2020 ). These findings offer a significant step toward the elimination of HIV-1 reservoirs in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Excision of HIV-1 proviral DNA in solid tissues and organs in humanized mice with chronic HIV-1 infection can be achieved via AAV-delivered CRISPR/Cas9 ( Yin et al, 2017 ). According to a recent study, AAV9-CRISPR/Cas9 gene editing was designed to eliminate simian immunodeficiency virus (SIV) proviral DNA in ART-treated non-human primates ( Mancuso et al, 2020 ). These findings offer a significant step toward the elimination of HIV-1 reservoirs in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…CRISPR/Cas9, a popular gene-editing tool, has been recently shown to treat HIV effectively in vitro [58][59][60][61][62][63][64][65][66][67] and animal models when administered in combination with antiretroviral therapy 68,69 . This tool is being refined to cope with HIV genetic diversity, off-target effects, harmful effects of large and dramatic genome rearrangements, generation of escape variants due to Cas9-induced mutants [62][63][64][65][70][71][72] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in HIV transgenic mice, humanized BLT mice infected with HIV, and SIV infected macaques have shown that AAV9 or AAV-DJ vectors expressing the Sa Cas9 gene in combination with sgRNAs that target the HIV or SIV long terminal repeat (LTR), and/or HIV gag can be used to excise portions of the HIV provirus in vivo when delivered systemically. HIV provirus excision was demonstrated in these studies in whole blood, CD4+ T cells, lymphoid, and non-lymphoid tissues throughout the body following a single AAV vector infusion [ 16 , 182 , 183 ], and up to 80% of SIV provirus DNA was lost from lymph nodes in SIV infected rhesus macaques that were pre-screened to be negative for exposure to AAV9 [ 16 ]. These studies suggest that with further work to identify new capsids with better in vivo tropism, effective AAV-mediated anti-HIV gene therapy could one day be a reality.…”
Section: Section Iv: Identification Of Cd4+ T Cell Tropic Aav Vectorsmentioning
confidence: 99%
“…Similarly, the delivery of gene editing technologies to inactivate and eliminate viral reservoirs that enable persistent/chronic infections has recently gained substantial attention [ 10 14 ]. Indeed, recent reports of viral genome elimination using meganucleases and CRISPR/Cas9 in animal models for HSV and HIV chronic infection, respectively, support the use of AAV vectors as a treatment for chronic viral infections [ 10 , 15 , 16 ]. The AAV-mediated delivery of antiviral therapies is not limited to gene-editing enzymes.…”
Section: Introductionmentioning
confidence: 99%